The effects of active queue management on web performance. - Le, Long (Computer communication review.)
We present an empirical study of the effects of active queue management (AQM) on the distribution of response times experienced by a population of web users. Three prominent AQM schemes are considered: the Proportional Integrator (PI) controller, the Random Exponential Marking (REM) controller, and Adaptive Random Early Detection (ARED). The effects of these AQM schemes were studied alone and in combination with Explicit Congestion Notification (ECN). Our major results are: # For offered loads up to 80% of bottleneck link capacity, no AQM scheme provides better response times than simple drop-tail FIFO queue management. # For loads of 90% of link capacity or greater when ECN is not used, PI results in a modest improvement over drop-tail and the other AQM schemes. # With ECN, both PI and REM provide significant response time improvement at offered loads above 90% of link capacity. Moreover, at a load of 90% PI and REM with ECN provide response times competitive to that achieved on an unloaded network. # ARED with recommended parameter settings consistently resulted in the poorest response times which was unimproved by the addition of ECN. </ol.We conclude that without ECN there is little end-user performance gain to be realized by employing the AQM designs studied here. However, with ECN, response times can be significantly improved. In addition it appears likely that provider links may be operated at near saturation levels without significant degradation in user-perceived performance.